EDUKASI TERHADAP PEMANFAATAN LIMBAH PLASTIK PADA ANAK-ANAK DI BIMBINGAN BELAJAR AL KHAWARIZMI - Awaliyah, Annisa Nurhafizah; Januarfi, Bella; Noviani, Ega (AbdiMuh : Jurnal Pengabdian Masyarakat, 2024)
The proliferation of MSMEs in every city and village area in the Bangka Belitung Islands has caused an increase in inorganic waste which causes problems for the environment. In this case, the activities of the Student Program in Education on the Use of Plastic Waste, which recycles waste, are very beneficial, apart from reducing environmental pollution, it can also be recycled so that it has high value. This plastic waste utilization activity was carried out at the Al Khawarizmi tutoring. The methods used in this activity are lecture, discussion and practice methods. After carrying out the waste recycling process, children can use plastic waste independently at home. Parents are also very enthusiastic when their children take part in these activities.